El dependiente - Favio, Leonardo; Jury, Zuhair Jorge; Vidarte, Walter, 1933-; Borges, Graciela; Cullen, Nora, 1905-1990; Notucan S.C.A.; Contracuadro (Firm); 3C Films Group ([Buenos Aires, Argentina] : Notucan S.C.A., 1969)
An employee of a hardware store, who has a dream of someday inheriting the business he has worked so hard to build, is under the close scrutiny of the owner. The worker meets a repressed woman who lives in a fantasy world and is controlled by a domineering mother. The two are entangled in a dark and ever increasingly tangled web.
Originally released as a motion picture in 1969.
Movie distributed by 3C Films Group for Digitalia Film Library.
Graciela Borges, Walter Vidarte, Nora Cullen.
Director of photography, Anibal di Salvo; editor, Antonio Ripoll; music, Vico Berti, Yaco Seller.
Based on a novel by Zuhair Jury.
In Spanish.
Keywords: Clerks -- Argentina -- Drama; Avarice -- Drama; Man-woman relationships -- Drama; Fiction films; Feature films; Internet videos; Streaming video